A Comment on "A Multidimensional Analysis of Selected Ethical Issues in Accounting" - Jones, Scott K.; Ponemon, Lawrence A. (The Accounting Review, 1993)
The article focuses on a comment on the paper "A Multidimensional Analysis of Selected Ethical Issues in Accounting," by S. M. Flory and others that was published in a previous issue of the journal "The Accounting Review." Their motivation was to investigate factors that might influence ethical behavior, realizing that these factors are potentially complex and multifaceted. Their overall conclusion was that the scale was highly reliable and valid, and thus should be a potentially useful tool for directing research on why accountants make certain ethical judgments. However, by failing to incorporate or expressly consider a psychological framework for the ethical reasoning process, the multidimensional ethics scales developed by Flory et al. do not provide any insight into the fundamental question on what makes accountants more or less ethical, and by the very nature of the research design, the otherwise well-chosen measures of reliability and validity are biased toward high measurement scale reliability.